Fermentation properties and functional stability of dough starter Jiaozi and Laomian after frozen storage - Li, Haifeng; Lv, Yulan; Zhang, Yingmiao; Wang, Xifeng; Yang, Xiaohong; Qu, Jianhang (Frontiers in Microbiology, 2024)
Purpose This study aims to investigate the effects of frozen storage on the stability of traditional dough starters in China. Methods The microbial community structure and abundance of related metabolic genes in different fermented sourdough prepared by Jiaozi (JZ) and Laomian (LM) starters before and after frozen storage at −20°C for half a year were analyzed using the shotgun metagenomic sequencing method, and differences in characteristics of texture in steamed bread were also compared by formal methods. Results The fermentation ability (FA) and metabolic activities of yeast in the JZH sourdough (started by JZ which was stored at −20°C for half a year) were better than those of LMH sourdough (started by LM which was stored at −20°C for half a year). The dominant genera of Acetobacter were found to be increased in the JZH0 sourdough (started by JZH and fermented for 0 h) and those of Lactobacillus were found to be decreased. Lactobacillus (98.72%), Pediococcus (0.37%), Saccharomyces (0.27%), and Acetobacter (0.01%), were dominant in sourdough LMH0 (started by LMH and fermented for 0 h). The abundances of “oxidative phosphorylation-related enzymes” and the “biosynthesis of glutamate”-related enzymes and genes related to “biosynthesis of glutamate” and “unsaturated fatty acid” were higher in JZH0 than in the JZ0 sourdough (started by JZ without being frozen and fermented for 0 h). The good FA of yeast, the acid production capacity of bacteria in the sourdough, and the quality of the JZH steamed bread (made by the JZH starter) indicated the better freezing tolerance of the microorganisms in JZ than in LM. Conclusion The conclusion of this study suggests the better application potential of the JZ as the fermentation starter in actual production.